Characterization of Pathogens Community in Women with Vaginal Infections - Teeba T. Kudair,; Mohammed Hashim Al-yasiri,; Ahmed K. Atya, (University of Thi-Qar Journal of Science, 2021)
Vagina organ of women is colonized by a variety of pathogenic and non-pathogenic microorganisms. Bacteria and fungi were the main microbial species isolated from vaginal infections. This study aimed to evaluate the microbial community in patients with vaginal infections and test their resistance to locally used antibiotics. 100 vaginal swabs were collected from married and non-pregnant women suffering from vaginitis who attended to Bent El-Huda Children Teaching Hospital at Thi-Qar province, Iraq. The collection period was from March to October 2019. The patients ages ranged between (15-55) years. Swabs were transported to the laboratory, and directly cultured on specific Culture media. All microbial species were identified using Traditional morphological and biochemical identification tests as well as Vitek 2. Microbial resistance was tested against 15 antibiotics. Number of infected women have increased in age 15 to 40 years, and then decreased from 41 years. A total of 84 bacterial isolate (gram positive and negative) and 33 Candida spp. were identified and tested against 15 antibiotics to show their resistance profiles. High diversity and abundance of bacterial species were observed, some of them were resistant to locally used antibiotics. Candida species were also resistant to fluconazole. In concluded, the prevalence of bacterial and yeast pathogens with antibiotics and antifungal resistance poses a health problem among married women. Therefore, Commitment to hygiene and avoid indiscriminate use of antibiotics are very necessary.